Formulation and Characterization of Gelatin Nanoparticles from Manis Rejo Leaf Extract (Vaccinium variangiaefolium (Bl.) Miq.) with Glutaraldehyde Concentrations Variations as Crosslinker - Yulius Evan Christian (Universitas Lambung Mangkurat, 2026)
Manis Rejo (Vaccinium variangiaefolium (Bl.) Miq.) is a plant that dominates at the Tangkuban Parahu area and grows in mountainous regions. Its leaves contain flavonoids with various benefits. The ethyl acetate extract of these leaves has demonstrated cytotoxic activity, making it a potential active compound in nanoparticle-based drug delivery systems. This study aimed to investigate the effect of variations in the glutaraldehyde concentration on the characteristics of the gelatination nanoparticles encapsulating the Manis Rejo leaf extract. The organoleptic properties, moisture content, and solubility of the extract were evaluated and then developed into nanoparticles (NPs) using the desolvation method with glutaraldehyde concentrations of 100 µl, 200 µl, and 300 µl. The characterization included the nanoparticle stability, particle size, polydispersity index (PDI), zeta potential, and morphology. The results showed that the extract was green, had a distinctive odor, a dry texture, a moisture content of 4.31%, and was soluble in ethyl acetate (1:10). The nanoparticles remained physically stable for 20 days at room temperature (25 oC), with particle sizes of 343.4±4.4 nm, 226.3±23.1 nm, and 199.7±1.6 nm, and PDIs of 0.381±0.0234, 0.446±0.0895, and 0.177±0.0195, respectively. The zeta potential values ranged from 15.8±1.1 to 17.8±1.1 mV. Transmission Electron Microscopy (TEM) analysis of formula III revealed a spherical morphology supporting the nanoparticle stability. Glutaraldehyde variation significantly influenced the particle size and PDI.